Multidrug resistant lncRNA profile in chemotherapeutic sensitive and resistant ovarian cancer cells. Issue 6 (2nd January 2018) - Xu, Juan; Wu, Jiacong; Fu, Chenyang; Teng, Fang; Liu, Siyu; Dai, Chencheng; Shen, Rong; Jia, Xuemei
Abstract : Most ovarian cancer patients are chemosensitive initially, but finally relapse with acquired chemoresistance. Multidrug‐resistance is the extremely terrible situation. The mechanism for the acquired chemoresistance of ovarian cancer patients is still not clear. LncRNAs have been recognized as the important regulator of a variety of biological processes, including the multidrug‐resistant process. Here, we carried out the lncRNA sequencing of the ovarian cancer cell line A2780 and the paxitaxel resistant cell line A2780/PTX which is also cross resistant to the cisplatin and epirubicin. Through integrating the published data with the cisplatin resistant lncRNAs in ovarian cancer cell line or ovarian cancer patients, 5 up‐regulated and 21 down‐regulated lncRNAs are considered as the multidrug‐resistant lncRNAs. By real‐time PCR analysis, we confirmed the 5 up‐regulated and 4 down‐regulated multidrug resistant lncRNAs were similarly changed in both the multidrug resistant ovarian cancer cell lines and the multidrug resistant colon cancer cell lines. Furthermore, we conducted the lncRNA‐mRNA co‐expression network to predict the potential multidrug resistant lncRNAs' targets. Interestingly, the multidrug resistant genes ABCB1, ABCB4, ABCC3, and ABCG2 are all co‐expressed with lncRNA CTD‐2589M5.4. Our results provide the valuable information for the understanding of the lncRNA function in the multidrug resistant process. Abstract : We carried out the lncRNA sequencing of the ovarian cancer cell line A2780 and the paxitaxel resistant cell line A2780/PTX which is also cross resistant to the cisplatin and epirubicin. Finally, five up‐regulated and four down‐regulated multidrug resistant lncRNAs was confirmed to be consistently changed in both the multidrug resistant ovarian cancer cell line and colon cancer cell line.